Unenhanced MR Angiography of the Foot: Initial Experience of Using Flow-Sensitive Dephasing–prepared Steady-State Free Precession in Patients with Diabetes - Liu, Xin (Radiological Society of North America, 2014)
PURPOSE: To assess image quality and diagnostic performance of unenhanced magnetic resonance (MR) angiography with use of flow-sensitive dephasing (FSD)–prepared steady-state free precession (SSFP) of the foot arteries in patients with diabetes. MATERIALS AND METHODS: This prospective study was approved by institutional review board. Informed consent was obtained from all subjects. Thirty-two healthy volunteers and 38 diabetic patients who had been scheduled for lower-extremity contrast material–enhanced MR angiography were recruited to undergo unenhanced MR angiography with a 1.5-T MR unit. Image quality and diagnostic accuracy of unenhanced MR angiography in the detection of significant arterial stenosis (≥50%) were assessed by two independent reviewers. Contrast-enhanced MR angiography was used as the reference standard. The difference in the percentage of diagnostic arterial segments at unenhanced MR angiography between healthy volunteers and diabetic patients was evaluated with the McNemar test and generalized estimating equation for correlated data. Signal-to-noise ratio (SNR) and artery-to-muscle contrast-to-noise ratio (CNR) of pedal arteries were measured and compared between the two MR angiography techniques by using the paired t test. RESULTS: All subjects successfully underwent unenhanced MR angiography of the foot. Unenhanced MR angiography yielded a high percentage of diagnostic arterial segments in both healthy volunteers (303 of 320 segments, 95%) and patients (341 of 370 segments, 92%), and there was no difference in the percentage between the two populations (P = .195). In patients, the average SNR and CNR at unenhanced MR angiography were higher than those at contrast-enhanced MR angiography (SNR: 90.7 ± 38.1 vs 81.7 ± 34.7, respectively, P = .023; CNR: 85.2 ± 33.2 vs 76.6 ± 33.5, respectively, P = .013). The average sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of unenhanced MR angiography were 88% (35 of 40 segments), 93% (107 of 115 segments), 81% (35 of 43 segments), 96% (107 of 112 segments), and 92% (142 of 155 segments), respectively. Interobserver agreement between the two readers for diagnostic accuracy was good (κ = 0.83). CONCLUSION: Unenhanced MR angiography with use of FSD-prepared SSFP allows clear depiction of the foot arterial tree and accurate detection of significant arterial stenosis. The technique has the potential to be a safe and reliable screening tool for the assessment of foot arteries in diabetic patients without the use of gadolinium-based contrast material. © RSNA, 2014